Bisdechlorogeodin from antarctic Pseudogymnoascus sp. LAMAI 2784 for citrus canker control - Ferrarezi, Juliano H. [UNESP]; Marin, Vítor R. [UNESP]; Vieira, Gabrielle [UNESP]; Ferreira, Henrique [UNESP]; Sette, Lara D. [UNESP]; Sass, Daiane C. [UNESP] (Oxford University Press (OUP), 2024)
Aims: Citrus canker caused by Xanthomonas citri subsp. citri (X. citri) is a disease of economic importance. Control of this disease includes the use of metallic copper, which is harmful to the environment and human health. Previous studies showed that the crude extract from the fungus Pseudogymnoascus sp. LAMAI 2784 isolated from Antarctic soil had in vitro antibacterial action against X. citri. The aim of the present study was to expand the applications of this extract. Methods and results: In greenhouse assays, the crude extract was able to reduce bacterial infection on citrus leaves from 1.55 lesions/cm2 (untreated plants) to 0.04 lesions/cm2. Bisdechlorogeodin was identified as the main compound of the bioactive fraction produced by Pseudogymnoascus sp. LAMAI 2784, which inhibited bacterial growth in vitro (IC90 ≈ 156 μg ml−1) and permeated 80% of X. citri cells, indicating that the membrane is the primary target. Conclusion: The present results showed that the bioactive fraction of the extract is mainly composed of the compound bisdechlorogeodin, which is likely responsible for the biological activity against X. citri, and the main mechanism of action is the targeting of the cell membrane. This study indicates that bisdechlorogeodin has valuable potential for the control of X. citri.
Keywords: antarctica; greenhouse; mechanism of action; Pseudogymnoascus; Xanthomonas